AI adoption, green fintech, and digital financial literacy: effects on sustainability disclosure and firm performance - Diyah Pujiati (Manajemen dan Bisnis, 2026)
This study examines how the use of AI, Green FinTech, and digital financial literacy contribute to sustainability reporting and performance of manufacturing firms in Indonesia. Based on Resource-based, Stakeholder and Legitimacy theories, a complete model is developed and tested with sustainability reporting as a mediator and environmental regulations as a moderator. Data are collected from 233 managers  who have been purposefully sampled because of their involvement with financial accounting, fiscal control and ESG activities. The results of a Partial Least Square analysis show that AI adoption, Green FinTech, and digital financial literacy increase reporting on sustainable practices therefore increasing firm performance. The results suggest that the effect of sustainable reporting is not statistically significant, demonstrating that it has been only partially integrated into the reporting process. The results also demonstrate that reporting sustainability practices mediates the relationship between digital capabilities and firm performance, while environmental regulations increase the relationship between sustainability practices and firm performance. The study contributes to existing theory by extending the RBV and Stakeholder perspectives relative to digital transformation and sustainability practices